2021
DOI: 10.3389/fcell.2021.681790
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin N-Terminal Function in an Abdominal Aortic Aneurysm From Apolipoprotein E-Deficient Mice

Abstract: The cleavage of osteopontin (OPN) by thrombin results in an N-terminal fragment (OPN-N), which exposes a cryptic integrin-binding motif that promotes the adherence of cells, and plays a proinflammatory role. However, the effect of OPN-N on abdominal aortic aneurysm (AAA) remains unknown. The aim of this study was to investigate the expression of OPN-N in aortic tissue samples obtained from patients, who underwent acute aortic dissection (AD), and normal aorta, effect of OPN-N on angiotensin (Ang) II-induced AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Furthermore, miR-1281 antagomir partially reversed hsa_circ_0000729 knockdown-induced cell growth inhibition of NSCLC (Figure 4G-I). Since cleaved caspase 1, GSDME-N and IL-18 were known to be key mediators in pyroptosis, 16,17 it could be suggested that hsa_circ_0000729 knockdown-induced pyroptosis in NSCLC cells was through sponging miR-1281.…”
Section: Hsa_circ_0000729 Could Bind With Mir-1281mentioning
confidence: 99%
“…Furthermore, miR-1281 antagomir partially reversed hsa_circ_0000729 knockdown-induced cell growth inhibition of NSCLC (Figure 4G-I). Since cleaved caspase 1, GSDME-N and IL-18 were known to be key mediators in pyroptosis, 16,17 it could be suggested that hsa_circ_0000729 knockdown-induced pyroptosis in NSCLC cells was through sponging miR-1281.…”
Section: Hsa_circ_0000729 Could Bind With Mir-1281mentioning
confidence: 99%
“…SPP1 codes for the osteopontin protein, an important regulator of inflammation that has described functions in cardiovascular diseases[45]. SPP1 is more expressed in AAA tissue than controls, both in animal models and in humans, and it participates in AAA-associated extracellular matrix degradation[46,47] through the nuclear factor kappa B signaling pathway. It is also known that the SPP1 gene undergoes splicing and gives rise to 3 distinct isoforms osteopontin a, osteopontin b and osteopontin c, with specific characteristics, which have not been characterized in AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the SPP1 gene, we found six genetic variants (rs35893069 (MAF (T) = 0.1), rs6839524 (MAF (G) = 0.12), rs4754 (MAF (C) = 0.28), rs1126616 (MAF (T) = 0.27), rs1126772 (MAF (G) = 0.21), rs9138 (MAF (C) = 0.22)) with allele specific expression among the twelve AAA samples. As previously discussed, the SPP1 has been associated to AAA risk due to the role of the protein osteopontin, which it encodes, in the degradation of the extracellular matrix that is characteristic of AAA[46,47]. However, none of the six genetic variants were found to be significant in the previous GWAS[7], and therefore no association with allelic expression could be established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the diseased state, full‐length OPN is often cleaved into an N‐terminal fragment (∼50 kDa) and two C‐terminal fragments (∼18 and ∼16 kDa) (Hoac et al., 2018 ). N‐OPN could be the major active form to trigger a series of pathological changes (Hattori et al., 2021 ; Liu et al., 2021 ). However, the role of N‐OPN in kidney injury has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%